Dido’s foundation legend, archetypes of foundation myths in Eurasia and Neomythology in the nineteenth century Balkans. - Oikonomidis, Stavros (Ex Novo: Journal of Archaeology, 2022)
Dido’s foundation legend of Carthage survives as a basic archetype for numerous foundation legends of Eurasia throughout the Middle Ages. The stratagem of the ox-hide is repeatedly referred as main theme of the foundation of towns, cities, and kingdoms, from the British Islands to the Balkans and eastern Eurasia. By the time of the genesis of the new nation – states in the Balkans the Didonian archetype has been re-proposed in the case of the foundation of the town of Naoussa, in Northern Greece, now with the Ottoman conqueror of the Balkans playing the role of Dido. His name was Gazi Evrenoz Beg, a Greek renegade who appears in a Greek manuscript found in Naoussa with attributes and characteristics taken by the Graeco-Roman vernacular and written tradition. In this article is studied and analyzed the survival of the ancient myth in the modern times focusing on the reproduction of it in the nineteenth century Balkans.